ANALISIS POTENSI ENERGI DAN PENGURANGAN EMISI CO2 DENGAN PENGELOLAAN LIMBAH PETERNAKAN SAPI RAKYAT DI KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN - Rinda Gusvita; Dian Fajarika; Mika Margareta; Devia Gahana CA (Journal of Science and Applicative Technology, 2017)
Management of feedlot manure is becoming a larger responsibility as more regulations are imposed to protect water, both surface and groundwater, from manure contamination. Instead of using the manure for compost, feedlot owners can capture methane from the decomposing manure (and turn that into electricity or heat), or use the waste to produce liquid fuel. Biogas may also be called renewable natural gas because biogas can be used as a fuel source to produce electricity and heat like natural gas.This research converting energy generated from the measurement of total waste theoretically to be convert to electricity generated from the waste. Within the number of 19,398 total cows in Jati Agung Sub District husbandry has the potential to produce electric energy of 149,365.376 kwh per day or 15,836.79 mwh per year. The conversion from waste to electricity will reduce the number of total emission of 64,086.7464 tCO2 per year.